Decade of design: media framing of "intelligent design" as a religious / unscientific concept or a scientific / unreligious concept from 2000 to 2009 - York, Chance (Kansas State University, 2010)
The debate over human origins was a prominent fixture of U.S. news coverage during the first decade of the 21st century. During this period, U.S. news media featured regular portrayals of an all-out culture war between supporters of biological evolution and advocates of so-called “rival theories” of human origins. In the end, this war would cost American taxpayers millions of dollars in legal fees, confuse science students, divide communities with unparalleled animosities, and alter public policy at the city, county and state level. While there have been previous content analyses performed on U.S. newspaper coverage of evolution and its primary challenger, an idea called "intelligent design," these analyses have tended to be somewhat informal (Mooney & Nisbet, 2005) or lacking (Martin, et al., 2006). The following study addresses these gaps in the literature. Using content analysis, the following study examines hard news coverage of intelligent design presented in 12 U.S. newspapers of varying circulation size and storytelling influence. A final sample of 421 newspaper articles originally published between the years 2000 and the end of the year 2009 is analyzed herein. Results demonstrate that U.S. newspapers initially framed intelligent design as primarily a religious / unscientific concept, but that intelligent design was increasingly framed as a scientific / unreligious concept leading up to, during and after the landmark 2005 Kitzmiller v. Dover trial. Additionally, this study finds no significant differences in framing intelligent design as a religious / unscientific or scientific / unreligious concept by dedicated science reporters and non-science reporters.
Keywords: intelligent design; creationism; content analysis; media framing; science journalism; pseudoscience; Journalism (0391); Mass Communications (0708)